Substrate Binding Switches the Conformation at the Lynchpin Site in the Substrate-Binding Domain of Human Hsp70 to Enable Allosteric Interdomain Communication - Umehara, Kohei (Molecules, 2018)
The stress-induced 70 kDa heat shock protein (Hsp70) functions as a molecular chaperone to maintain protein homeostasis. Hsp70 contains an N-terminal ATPase domain (NBD) and a C-terminal substrate-binding domain (SBD). The SBD is divided into the β subdomain containing the substrate-binding site (βSBD) and the α-helical subdomain (αLid) that covers the βSBD. In this report, the solution structures of two different forms of the SBD from human Hsp70 were solved. One structure shows the αLid bound to the substrate-binding site intramolecularly, whereas this intramolecular binding mode is absent in the other structure solved. Structural comparison of the two SBDs from Hsp70 revealed that client-peptide binding rearranges residues at the interdomain contact site, which impairs interdomain contact between the SBD and the NBD. Peptide binding also disrupted the inter-subdomain interaction connecting the αLid to the βSBD, which allows the binding of the αLid to the NBD. The results provide a mechanism for interdomain communication upon substrate binding from the SBD to the NBD via the lynchpin site in the βSBD of human Hsp70. In comparison to the bacterial ortholog, DnaK, some remarkable differences in the allosteric signal propagation among residues within the Hsp70 SBD exist.